2010
DOI: 10.1016/s0210-4806(10)70036-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribución demográfica y prevalencia de la vejiga hiperactiva en Venezuela

Abstract: The OAB-V8 questionnaire aids to clearly identify patients with OAB symptoms. The overall prevalence of OAB in Venezuela is 21%. It is present in both genders, predominantly women and can be detected at early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We observed a probable OAB diagnosis in more than half of women using the OAB-V8 questionnaire. Davila et al ( 24 ) reported similar results (51%) using the same questionnaire, and also questioned the reliability of isolated use of this instrument for OAB diagnosis. Thus, if we consider only the OAB-V8 questionnaire our outcomes may be overestimated.…”
Section: Discussionmentioning
confidence: 82%
“…We observed a probable OAB diagnosis in more than half of women using the OAB-V8 questionnaire. Davila et al ( 24 ) reported similar results (51%) using the same questionnaire, and also questioned the reliability of isolated use of this instrument for OAB diagnosis. Thus, if we consider only the OAB-V8 questionnaire our outcomes may be overestimated.…”
Section: Discussionmentioning
confidence: 82%
“…In 2010, a multicentric assessment using the OAB-V8 questionnaire was conducted in Venezuela in a total of 3,407 18-75 year-old adults, with 38% of them being males. The prevalence of overactive bladder in this population was 21% ( 8 ). Other studies conducted in Latin America found a similar prevalence; 23.4% and 18.9%, in Argentina and Brazil, respectively ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 82%
“…In Finland, its prevalence in women was 9.3% and 6.5% in men ( 6 ). In Venezuela, the study revealed that women were more often affected than men – 25.6% and 13.7%, respectively ( 8 ). The same result was observed by Teloken et al, in Brazil, where the condition was reported by 23.3% of women and 14% of men ( 10 ), as well as Temml et al, with 16.8% of women and 10.2% of men reporting it ( 11 ).…”
Section: Introductionmentioning
confidence: 99%